2019
DOI: 10.1021/acsomega.9b02370
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis of Methane Oxidation through Modulating the Stabilization of PdO and Electronic Properties over Ti-Doped Alumina-Supported Palladium Catalysts

Abstract: Poor low-temperature catalytic activity and durability are the main drawbacks of palladium-based catalysts for methane combustion. Herein, stable and active PdO particles are constructed by incorporating Ti into an alumina support, which makes the catalysts exhibit satisfactory methane combustion activity. The results of comprehensive characterization reveal that an appropriate amount of Ti doping induces the optimization of electron transfer and distribution, thus contributing to the construction and stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…These results indicate that the Al20-HAP80-Pd catalyst has a high catalytic activity and high stability in ethanol dehydration for the production of diethyl ether and ethylene. According to Chen et al, 56 As a result, the interaction between Pd species and the Al 2 O 3 −HAP is enhanced, leading to the improvement of the thermal stability, we think which may be one reason for the good stability of the Al20-HAP80-Pd catalyst.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…These results indicate that the Al20-HAP80-Pd catalyst has a high catalytic activity and high stability in ethanol dehydration for the production of diethyl ether and ethylene. According to Chen et al, 56 As a result, the interaction between Pd species and the Al 2 O 3 −HAP is enhanced, leading to the improvement of the thermal stability, we think which may be one reason for the good stability of the Al20-HAP80-Pd catalyst.…”
Section: Resultsmentioning
confidence: 68%
“…These results indicate that the Al20-HAP80-Pd catalyst has a high catalytic activity and high stability in ethanol dehydration for the production of diethyl ether and ethylene. According to Chen et al, the incorporation of Pd into the lattice of Al 2 O 3 –HAP catalyst and displaces the Al 2 O 3 –HAP (calcium aluminate ion) sites to form [Al–HAP]–Pd + –O bonds, which increase the negative charge around the Al 2 O 3 –HAP. As a result, the interaction between Pd species and the Al 2 O 3 –HAP is enhanced, leading to the improvement of the thermal stability, we think which may be one reason for the good stability of the Al20-HAP80-Pd catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the TiO 2 's oxygen storing capability reduced the hysteresis between Pd reoxidation and PdO decomposition, stabilizing the PdO phase and speeding up the activation of CH 4 with a 90% conversion at 410 °C. [106] However, the poor stability of Pd/TiO 2 catalysts continues to be a major issue. [107] Recently, Xiao et al reported that a Pd catalyst supported on a reducible carrier TiO 2 via the sol-gel method and calcined 1000 °C could produce abundant Pd 2+ species, Ti 3+ , and oxygen vacancies on the surface, assisting the reoxidation of Pd 0 back to PdO and inducing a high activity toward combustion of CH 4 to CO 2 with a T 99 at 370 °C.…”
Section: Pd-based Catalystsmentioning
confidence: 99%
“…Additionally, the TiO 2 ’s oxygen storing capability reduced the hysteresis between Pd reoxidation and PdO decomposition, stabilizing the PdO phase and speeding up the activation of CH 4 with a 90% conversion at 410 °C. [ 106 ] However, the poor stability of Pd/TiO 2 catalysts continues to be a major issue. [ 107 ] Recently, Xiao et al.…”
Section: Thermocatalytic Activation Of Methanementioning
confidence: 99%